Recall, Precision, and F-Measure for Evaluating Information Retrieval System in Electronic Document Management Systems (EDMS) - Sadeli, Annisa Fajriyati; Lawanda, Ike Iswary (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2023)
The Legal Division of PT. ABC has implemented EDMS using the Integrated Legal Document Management Application, Centralized Legal Administration System (CLAS), to make the management of documents more accessible. The urgency is the system's accuracy in retrieving data or document input. The study employed a quantitative method with an experimental approach. Data collection techniques were observation, application search tests, documentation, and literature. Data analysis regarding the recall, precision, and F-measure calculation formulas will be compared with the standard information retrieval system effectiveness. The calculation results show that the average recall value for the search equals 1 or 100%. For the precision value that uses quotation marks, it is equal to 0.9713, while for searching without quotation marks, it is equal to 0.3920. From these results, the precision value is lower than the recall value. The precision value of 0.9713 is in the range of 0.68–1.00, which is placed as high precision, meaning that information retrieval is effective. The F-measure value is 0.98, close to 1, so the tracing system is sound. CLAS is quite effective in retrieving information according to user needs.